Tumour suppressor genes in chemotherapeutic drug response. Issue 4 (23rd April 2012) - Lai, Dulcie; Visser-Grieve, Stacy; Yang, Xiaolong
Abstract : Since cancer is one of the leading causes of death worldwide, there is an urgent need to find better treatments. Currently, the use of chemotherapeutics remains the predominant option for cancer therapy. However, one of the major obstacles for successful cancer therapy using these chemotherapeutics is that patients often do not respond or eventually develop resistance after initial treatment. Therefore identification of genes involved in chemotherapeutic response is critical for predicting tumour response and treating drug-resistant cancer patients. A group of genes commonly lost or inactivated are tumour suppressor genes, which can promote the initiation and progression of cancer through regulation of various biological processes such as cell proliferation, cell death and cell migration/invasion. Recently, mounting evidence suggests that these tumour suppressor genes also play a very important role in the response of cancers to a variety of chemotherapeutic drugs. In the present review, we will provide a comprehensive overview on how major tumour suppressor genes [Rb (retinoblastoma), p53 family, cyclin-dependent kinase inhibitors, BRCA1 (breast-cancer susceptibility gene 1), PTEN (phosphatase and tensin homologue deleted on chromosome 10), Hippo pathway, etc.] are involved in chemotherapeutic drug response and discuss their applications in predicting the clinical outcome of chemotherapy for cancer patients. We also propose that tumour suppressor genes are critical chemotherapeutic targets for the successful treatment of drug-resistant cancer patients in future applications.